2015
DOI: 10.1080/13607863.2014.1003287
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, stress, and life quality in older adults living with HIV/AIDS

Abstract: Objectives This study tested the mediating effect of resilience on the relationship between life stress and health-related quality of life (HRQoL) in older people living with HIV/AIDS (OPLWHA) 50 years of age and older. Method Data from 299 OPLWHA were analyzed using structural equation modeling (SEM) to define a novel resilience construct (represented by coping self-efficacy, active coping, hope/optimism and social support) and assess mediating effects of resilience on the association between life stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 42 publications
(45 reference statements)
4
82
0
3
Order By: Relevance
“…Understanding resilience among people living with HIV (PLHIV) is important because measures of higher resilience have previously been linked to lower levels of psychological and emotional distress [10,11], better health outcomes [10,12], and reductions in the negative effects of life stress on health-related quality of life among PLHIV [13]. Examples of HIV-positive gay men and other PLHIV displaying resilience while adapting to their HIV diagnosis or in the face of adversities such as discrimination have also been described in a number of qualitative studies [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding resilience among people living with HIV (PLHIV) is important because measures of higher resilience have previously been linked to lower levels of psychological and emotional distress [10,11], better health outcomes [10,12], and reductions in the negative effects of life stress on health-related quality of life among PLHIV [13]. Examples of HIV-positive gay men and other PLHIV displaying resilience while adapting to their HIV diagnosis or in the face of adversities such as discrimination have also been described in a number of qualitative studies [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, resilience intervention approach was positively correlated to self-esteem, where individuals were more capable of handling stressful events and experience personal growth during stressful situations (Dolbier, Jaggars & Steinhardt, 2010). Similar findings were presented by Fang et al, (2015), where participants with greater resilience, experienced better physical, emotional and functional wellbeing, indicating that resilience may diminish the negative effects of stress in this group.…”
Section: Resilience Processsupporting
confidence: 71%
“…In many other disease processes, wasting and/or low BMI are associated with poor QoL and decreased response to QoL interventions, so this was an unexpected finding [37–39]. Prior studies involving older HIV-infected adults have found a strong association between greater resilience and improved mental QoL [40]. Perhaps the greater mental QoL is due in part to a greater appreciation of survival following advanced disease, or to a realization of partial disease “remission” with continued HIV [41, 42],…”
Section: Discussionmentioning
confidence: 99%